Analisa Trombositosis, Leukositosis dan Kombinasi Trombositosis- Leukositosis terhadap Hasil RECIST 1.1, Progression Free Survival dan Stadium pada Pasien Karsinoma Paru Bukan Sel Kecil yang mendapatkan Kemoterapi Analisa Trombositosis, Leukositosis dan Kombinasi Trombositosis-Leukositosis terhadap Hasil RECIST 1.1, Progression Free Survival dan Stadium pada Pasien Karsinoma Paru Bukan Sel Kecil yang mendapatkan Kemoterapi - Wiyono, Hendri; Setyawan, Ungky Agus; Pratiwi, Suryanti Dwi (Jurnal Klinik dan Riset Kesehatan, 2025)
Background: Lung cancer is the most common malignancies that lead to highest mortality and morbidity. Advanced lung cancer is treated with chemotherapy and the evaluation is using RECIST. Thrombocytosis and or leukocytosis in lung cancer, theoritically stand with bad condition.The aim of this study is to analyse whether thrombocytosis and or leukocytosis can be a prognostic factor compare to the result of RECIST,Progression Free Survival and the stadium of lung cancer. Method: This study uses retrospective analytic cross-sectional design.Data were taken from medical record at Saiful Anwar Hospital,2018-2021,processed with Chi square,Mann-Whitney, and Fisher Exact test. Result:The result of Chi square Thrombocytosis and Leukocytosis to the first result of RECIST are ᵡ²(1) =59,659; p=0,000 and ᵡ²(1) = 5,707:p=0,017.To the median PFS 5,66 months the test are ᵡ²(1)=51,776:p=0,000; ᵡ²(1)=4,259:p=0,039.To the state of progression, the test are ᵡ² (1)=15,171:p=0,000; ᵡ²(1)=2,226:p=0,329.To stadium, Mann-Whitney test are:1145,00;Z= -1,026:p=0,305 and 1040,500;Z= -1,393:p=0,164. Conclusion: There is statistically significance between thrombocytosis or leukocytosis to the first result of RECIST,median PFS 5,66 months.No significance to the stadium of lung cancer.Thrombocytosis and or leukocytosis can be a prognostic factor for result of chemoteraphy.